2015
DOI: 10.1515/chem-2015-0124
|View full text |Cite
|
Sign up to set email alerts
|

Biomass of freshwater Cladophora as a raw material for agriculture and the cosmetic industry

Abstract: This study was undertaken to determine mineral content, amino acid and fatty acid composition of the freshwater macroalga -Cladophora glomerata. The studies were based on the content comparison in algal biomass collected from a lake and cultured in a laboratory. To determine the ability of copper cumulating by macroalgae, Cladophora was cultured in the medium supplemented with Cu ions. This study indicated that the relative abundance of metals in filaments decreased in the following order: Ca > K > Mg > Na > F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 23 publications
1
27
0
3
Order By: Relevance
“…The FAs can be mainly extracted from algal biomass using Soxhlet apparatus with organic solvent or SFE-CO 2 as a solvent [29][30][31]. It was noticed that SFE favored isolation of saturated and unsaturated fatty acids when compared to traditional extraction techniques with the use of organic solvents.…”
Section: Content Of Fas In the Raw Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FAs can be mainly extracted from algal biomass using Soxhlet apparatus with organic solvent or SFE-CO 2 as a solvent [29][30][31]. It was noticed that SFE favored isolation of saturated and unsaturated fatty acids when compared to traditional extraction techniques with the use of organic solvents.…”
Section: Content Of Fas In the Raw Materialsmentioning
confidence: 99%
“…It was noticed that SFE favored isolation of saturated and unsaturated fatty acids when compared to traditional extraction techniques with the use of organic solvents. Many studies showed that SFE is characterized by a higher efficiency of extraction of biologically active substances from a natural source when compared to other extraction techniques [31,32]. Table 3 presents the percentage weight of FA in dry matter of the samples that were used in laying hens feeding, i.e., microalga Spirulina platensis, formulation of SC-extract from S. platensis, post-extraction residue of S. platensis, and the formulation that was used to prepare the application form of supercritical extract.…”
Section: Content Of Fas In the Raw Materialsmentioning
confidence: 99%
“…creating a buffer zone, sediment dredging, application of algaecides) to prevent load of nutrients from agricultural lands into water bodies (weissteiner et al, 2013;iBisch et al, 2016;DonDaJewsKa et al, 2019). Prototypes for freshwater wild algal and cyanobacteria bio-mass harvesting have not been yet widely applied and only a few demonstrative practices usually excluding clear estimation of ecological and economic benefits have been provided worldwide (adey et al, 1993;water Facts, 1998;carMichael et al, 2000;GrönDahl, 2009;pechsiri et al, 2014;Messyasz et al, 2015;Pikosz et al, 2017). Nevertheless, several commercially available mechanical harvesters exist nowadays (Fig.…”
Section: Tasks and Targets Of The Project "Algae Service For Life"mentioning
confidence: 99%
“…Massive growth of macroalgae or cyanobacteria is the first sign that the water body has been affected. Extensive development of macroscopic algae in freshwaters creates the environmental and social problems in aquatic ecosystems due to formation of spatially large mats (Messyasz et al, 2015(Messyasz et al, , 2018. They can choke water body, clog irrigation pipes,…”
Section: Introductionmentioning
confidence: 99%
“…However, as it was shown, supercritical fluid extraction (SPE) with carbon dioxide which is considered as a ‘green solvent’ can be more efficient in the extraction of biologically active compounds than conventional techniques. The fatty acid content in the dry matter of the extract obtained from freshwater Cladophora glomerata varied depending on the extraction method used: ethylene alcohol (19%), acetone (35%) or SPE (63%) . Schroeder et al .…”
Section: Introductionmentioning
confidence: 99%